2021
DOI: 10.1002/nop2.967
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study about cancer outpatients’ experiences with selective taste control of bread as a self‐care intervention

Abstract: Alterations in taste and food hedonics are distressing side effects noted in people with cancer receiving chemotherapy (Gamper et al., 2012;Spotten et al., 2017). These side effects have several consequences. In their systematic review Boltong and Keast (2012) point out the negative effects on nutritional status, quality of life, morbidity and mortality (Boltong & Keast, 2012). In a recent literature review, Spotten et al. (2017) stress that malnutrition, among others, is a predictor of mortality and treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Milzer et al (2022) demonstrated that the boundary-setting activity of recording patterns of fatigue in a diary helps to shape new daily routines during recovery. Corremans et al’s (2022) consideration of food hedonics demonstrates how this could encourage task-focused social interaction based on curiosity and decentralize dialogue around the “suffering patient” (p. 2685). In this study, participants used everyday objects to accommodate or place boundaries around symptoms, placed value on small acts of hedonism or creative displacement activities (reflected in Howard-Jones et al, 2021), and re-invested in existing emotional connections (a key factor also evidenced by Sieverding et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Milzer et al (2022) demonstrated that the boundary-setting activity of recording patterns of fatigue in a diary helps to shape new daily routines during recovery. Corremans et al’s (2022) consideration of food hedonics demonstrates how this could encourage task-focused social interaction based on curiosity and decentralize dialogue around the “suffering patient” (p. 2685). In this study, participants used everyday objects to accommodate or place boundaries around symptoms, placed value on small acts of hedonism or creative displacement activities (reflected in Howard-Jones et al, 2021), and re-invested in existing emotional connections (a key factor also evidenced by Sieverding et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent knowledge about the incidence and prevalence of chemotherapy-induced taste alterations may enable tailored food interventions 23 . The description of variations in taste changes in subgroups of chemotherapy is important to inform the dissemination of taste steering interventions.…”
Section: Introductionmentioning
confidence: 99%